Gene Polymorphism Vitamin D receptor BsmI in Thalassemia Children in Al-Muthanna Province (Indian Journal of Forensic Medicine & Toxicology, 2020)
Introduction: Vitamin D is crucial for calcium, phosphate homeostasis and mineralization of the skeleton,particularly through growth time developments. Vitamin D deficiency lead to rickets in children andosteoporosis in adult. The activity of vitamin D receptors (VDR) are responsible for the vitamin D sothat the single nucleotide polymorphism was detected using BsmI. Material and methods: In this study,the vitamin D3 level were measured using enzyme-linked sorbent assay (ELISA) technique, followed bydetection of the polymorphism VDR- BsmI gene using PCR and BsmI restriction enzyme assay (PCRRFLP). Results: Vitamin D, alkaline phosphate and others biochemical were performed in 50 patients betathalassemia were divided into 25 males and same number females. The biochemical results demonstrated nosignificant difference p<0.05 between males and females according gender, whereas showed high significantserum calcium p value 0.048 according body mass index. We using RFLP-PCR technique to amplify VDRgene BsmI, DNA ladder molecular weight was 1000-2500 base pair and BsmI digestion showing predictedproduct in 823 to 175 pb in all lane. Conclusions: BsmI digestion was showing heterozygous mutant (Bb)and homozygous (BB). These result gene polymorphism VDR BsmI effected on vitamin D levels and relatedwith bone diseases and process metabolism.